Treatment of proximal humeral fractures using anatomical locking plate: correlation of functional and radiographic results - Antonio Carlos Tenor Junior; Alisson Martins Granja Cavalcanti; Bruno Mota Albuquerque; Fabiano Rebouças Ribeiro; Miguel Pereira da Costa; Rômulo Brasil Filho (Revista Brasileira de Ortopedia, 2016)
ABSTRACT OBJECTIVE: To correlate the functional outcomes and radiographic indices of proximal humerus fractures treated using an anatomical locking plate for the proximal humerus. METHODS: Thirty-nine patients with fractures of the proximal humerus who had been treated using an anatomical locking plate were assessed after a mean follow-up of 27 months. These patients were assessed using the University of California Los Angeles (UCLA) score and their range of motion was evaluated using the method of the American Academy of Orthopedic Surgeons on the operated shoulder and comparative radiographs on both shoulders. The correlation between radiographic measurements and functional outcomes was established. RESULTS: We found that 64% of the results were good or excellent, according to the UCLA score, with the following means: elevation of 124°; lateral rotation of 44°; and medial rotation of thumb to T9. The type of fracture according to Neer's classification and the patient's age had significant correlations with the range of motion, such that the greater the number of parts in the fracture and the greater the patient's age were, the worse the results also were. Elevation and UCLA score were found to present associations with the anatomical neck-shaft angle in anteroposterior view; fractures fixed with varus deviations greater than 15° showed the worst results (p < 0.001). CONCLUSION: The variation in the neck-shaft angle measurements in anteroposterior view showed a significant correlation with the range of motion; varus deviations greater than 15° were not well tolerated. This parameter may be one of the predictors of functional results from proximal humerus fractures treated using a locking plate.